Microwave Assisted Co/SiO2 preparation for Fischer-Tropsch synthesis - TEUKU MUKHRIZA; KUI ZHANG; ANH N. PHAN (Universitas Syiah Kuala, 2020)
Cobalt catalyst has been widely used for Fischer-Tropsch (FT) Synthesis in Industry. The most common method to prepare cobalt catalyst is impregnations. Metal is deposited on porous support by contacting dry support with solution containing dissolved cobalt precursor. This step will follow by drying, calcination and reduction. The heating step used in this conventional method, however, may lead to the formation of metal silicate which is inactive site for catalysis. In this study, author explore the use of microwave to prepare catalyst compared to conventional drying method. Cobalt catalyst with SiO2 support was prepared and characterized. Particle size, surface area, and cobalt content were investigated. Crystallite size of 3-8 nm was formed which was reported to be the optimum size for cobalt catalyst in FT Synthesis. Scanning Electron Microscope (SEM) and Transmission Electron Microscopy (TEM) image revealed that microwave catalyst showed better uniformity and cobalt dispersion on silica support. Thermo-Gravimetric Analysis (TGA) study also indicated that this catalyst has good stability at Low Temperature Fischer-Tropsch Synthesis. The catalysts were then applied plasma assisted FT process over a range of power plasma (20-60W) to investigate the effect on the conversion and selectivity. The results showed that microwave catalyst exhibit lower CO conversion at 42.06% compared to conventional method at 68.32%. However, microwave catalyst is more favourable for long chain hydrocarbon selectivity.